A geoportal of data and tools for supporting Maritime Spatial Planning in the Adriatic-Ionian Region. (February 2023) - Menegon, Stefano; Fadini, Amedeo; Perini, Luisa; Sarretta, Alessandro; Depellegrin, Daniel; De Maio, Elisabeth; Farella, Giulio; Landini, Marica; Fava, Carlo; Ferrarin, Christian; Ghezzo, Michol; Manea, Elisabetta; et al.
Abstract: The multiple anthropogenic threats to marine ecosystems and the increasing spatial conflicts in the Adriatic-Ionian Region (AIR) require transnational, integrated and efficient planning of coastal and marine spaces at macro-regional level. This research presents the Geoportal of the Adriatic-Ionian Region (GAIR), a common platform for information, data and decision support tools for ocean planning in the Adriatic-Ionian sea space. The GAIR is an open source platform; it supports co-production of MSP-relevant knowledge based on 12 databases, portals and tools developed within a set of European projects supporting the implementation of the European Strategy for the AIR (EUSAIR). The study presents the GAIR's software architecture, its technological stack and the seven integrated geospatial tools. A case study of the tool presents its user workflow and main outputs. The paper concludes with an evaluation of the GAIR with respect to MSP, Sustainable Blue Economy and the implementation of the EUSAIR Action Plan. Graphical abstract: Image 1 Highlights: The GAIR is an open source platform for MSP in the Adriatic-Ionian Region. The technological stack adopts Free and Open Source (FOSS) principles. 7 geospatial tools for single and multi-sectoral analysis were developed. The platform is tested for cumulative effects assessment in Emilia Romagna Region. The design of the platform supports data-sharing and transnational cooperation.